Palliative patient safety - Tânia dos Santos Afonso; Lurdes Martins; Manuel Luís Capelas (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2018)
Introduction: The palliative patient is more predisposed to the consequences of the error situations. Aim: To understand patient safety in the context of palliative. Materials and Methods: Integrative literature review which included studies of the last eleven years, using descriptors from Medline, CINAHL Plus with Full Text, and the Portuguese Open Access Scientific Repository. We consider the research question: What is meant by patient safety in need of palliative care? Results: The 11 selected articles develop aspects of user safety around symptomatic control, medication errors, the incidence of home safety, quality of care, route of administration, and palliative sedation. Conclusion: Predominance of the association between safety and mention of errors in medication use. Emerges a suggestion to create an error notification system in a palliative context.